Analysis of the Impact of 12% VAT Implementation on the Indonesian Economy: An Empirical Study of the U-Shaped Impact Phenomenon on Public Purchasing Power in the January-June 2025 Period - Putri, Wenti Frisca Septiani; Oroh, Oliviane; Maulana, Dikdik (Yayasan Kawanad, 2025)
This study examines the economic impacts of Indonesia's 12% Value Added Tax (VAT) during January-June 2025 using a Difference-in-Differences (DiD) approach. The VAT increase from 11% to 12%, effective January 1, 2025, aims to boost state revenue and support post-pandemic economic recovery. Analysis draws on time series data from Statistics Indonesia (BPS), Bank Indonesia, and the Ministry of Finance, along with household surveys and MSME data. Results show that the 12% VAT added 0.45 percentage points to national inflation, with manufacturing bearing the largest burden at 0.18 percentage points. A striking U-shaped pattern emerged in purchasing power effects: middle-income groups (quintile 3) suffered the steepest decline of 3.4%, while low and high-income groups experienced smaller reductions. The VAT exhibits regressive characteristics, pushing the Gini coefficient from 0.381 to 0.394 and raising poverty rates from 9.54% to 9.78%—forcing approximately 640,000 people below the poverty line. While state revenue increased by 18.7%, mitigation interventions worth 0.3-0.5% of GDP became necessary. The study recommends targeted mitigation strategies: focused social compensation, revised VAT-exempt goods lists, and integrated progressive tax reforms.